2010
DOI: 10.1002/dys.416
|View full text |Cite
|
Sign up to set email alerts
|

Reading and visual processing in Greek dyslexic children: an eye-movement study

Abstract: We examined the impact of the effects of dyslexia on various processing and cognitive components (e.g., reading speed and accuracy) in a language with high phonological and orthographic consistency. Greek dyslexic children were compared with a chronological age-matched group on tasks that tested participants' phonological and orthographic awareness during reading and spelling, as well as their efficiency to detect a specific target-letter during a sequential visual search task. Dyslexic children showed impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 63 publications
(61 reference statements)
4
10
0
6
Order By: Relevance
“…Similar findings have been reported in previous studies in consistent orthographies (e.g. Bekebrede, van der Leij, & Share, 2009;Bergmann & Wimmer, 2008;Hatzidaki, Gianneli, Petrakis, Makaronas, & Aslanides, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings have been reported in previous studies in consistent orthographies (e.g. Bekebrede, van der Leij, & Share, 2009;Bergmann & Wimmer, 2008;Hatzidaki, Gianneli, Petrakis, Makaronas, & Aslanides, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in Chinese dyslexic children, Li et al [7] reported abnormal eye movements in picture searching, slow and more fixations and frequent saccades of small amplitude. Recently, Trauzettel-Klosinski et al [8] reported in German dyslexic children slower reading speed and high number of saccades and regressions; similar findings have been also reported in Greek dyslexic children by Hatzidaki et al [9].…”
Section: Introductionsupporting
confidence: 61%
“…Consistent with findings in other languages, studies of Greek children with dyslexia have documented deficits in phonological awareness, word and pseudoword reading accuracy and speed, spelling, rapid automatized naming, stress assignment, and verbal working memory, through primary and secondary education (Anastasiou & Protopapas, ; Constantinidou & Evripidou, ; Constantinidou & Stainthorp, ; Diamanti, Goulandris, Stuart, & Campbell, ; Hatzidaki, Gianneli, Petrakis, Makaronas, & Aslanides, ; Papadopoulos, Georgiou, & Kendeou, ; Protopapas et al, ; Protopapas & Skaloumbakas, , ; Protopapas, Skaloumbakas, & Bali, ). As expected for a relatively consistent orthography, children with dyslexia are primarily distinguished from typically developing readers in timed measures of reading (i.e., speed or fluency; Protopapas & Skaloumbakas, ) and exhibit impaired spelling performance commensurate with their level of reading and phonological development (Diamanti et al, ; Protopapas et al, ).…”
Section: Introductionsupporting
confidence: 53%